Dorsal root ganglion pulsed radiofrequency using bipolar technology in patients with lumbosacral radicular pain duration ≥ 2 years - Luo, Qipeng; Zhao, Zifang; Yi, Duan; Li, Shuiqing; Liu, Xiaoguang (Frontiers in Neuroscience, 2022)
Background Transforaminal epidural steroid injection (TFESI) or dorsal root ganglion pulsed radiofrequency (PRF) are alternative treatments for lumbosacral radicular pain (LSRP). This study aimed to investigate the clinical efficacy of TFESI combined with dorsal root ganglion PRF using bipolar technology to treat LSRP in patients with pain duration ≥ 2 years. Methods This prospective single-armed cohort study included 20 patients with LSRP duration ≥ 2 years, who underwent treatment of TFESI combined with bipolar PRF. The primary outcomes included numerical rating scale (NRS) and successful treatment rate (pain relief ≥50%). The secondary outcomes included Oswestry Disability Index (ODI), patient satisfaction using the modified MacNab criteria, severe complications, hospital stay and total costs. The final follow-up was 6 months postoperatively. Results The successful treatment rate and average pain relief at 6 months postoperatively were 80% and 73.0% ± 17.5%, respectively. The successful treatment rates in patients with and without prior intervention history at 6 months postoperatively were 77.8% and 81.8%, respectively. The mean NRS score significantly decreased from 6.5 ± 0.8 to 1.1 ± 0.7 at 2 weeks postoperatively, to 1.3 ± 0.7 at 3 months postoperatively, and to 1.7 ± 1.0 at 6 months postoperatively (all P < 0.001), while the mean ODI score significantly decreased from 43.5 ± 2.5 to 22.5 ± 4.3 at 2 weeks postoperatively, to 20.0 ± 3.5 at 3 months postoperatively, and to 19.5 ± 3.6 at 6 months postoperatively (all P < 0.001). The excellent and good patient satisfaction at 6 months postoperatively was 85%. No severe complications were observed in this cohort. The average hospital stay and total costs were 3.0 ± 0.5 days and 3.36 ± 0.77 thousand dollars, respectively. Conclusion The treatment of TFESI combined with PRF using bipolar technology might be an alternative option to treat chronic LSRP in patients with pain duration ≥ 2 years after a failure of conservative treatments, with a favorable 6-month efficacy and inexpensive total costs. However, long-term outcomes and superiority of bipolar procedure over monopolar procedure in patients with longer pain duration should be further investigated in future studies.